Choices of sampling method bias functional components estimation and ability to discriminate assembly mechanisms. Issue 6 (8th April 2019) - Lee, Roger H.; Guénard, Benoit
Abstract: The understanding and prediction of species distributions have been advanced by the development of community assembly theories and functional trait‐based approaches. Coupled with null models, trait dispersion patterns are commonly used to gauge the relative importance of niche versus neutral‐based processes on shaping local communities. However, asymmetrical trait dispersion patterns of identical communities may artificially arise as a result of sampling methods choice. This non‐random filtering on traits is overlooked, and it may bias the estimation of functional components as well as the detection of underlying assembly mechanisms—especially for species‐rich arthropod communities. We sampled subtropical ground‐dwelling ant communities using a paired treatment design comprising pitfall traps and Winkler extractors (Winklers), two commonly used sampling techniques for terrestrial arthropods, in 17 shrublands and 33 secondary forest 400 m 2 plots in Hong Kong to determine the effect of sampling filters on functional composition (community means of six morphological traits) and functional diversity (range and variance of individual traits; size and filling properties of multidimensional trait space) using a null model approach for each habitat. We found, as hypothesized, that sampling filters from different methods affected the trait composition and diversity of ant communities asymmetrically. In shrublands and forests, the trait compositions of communities sampled by pitfall traps were dominated by larger sized, slender‐shaped and long‐legged ants as compared to those sampled by Winklers. The latter method also underestimated the diversity of individual traits related to body size as well as the size and filling properties of multidimensional trait space. Our results highlight that the usage of particular sampling methods without prior knowledge on their potential filtering effects on traits can affect the detection of assembly processes, and interpretation of functional proxies, such as body size. Additional care should be taken when comparing trait components obtained from studies using different sampling methods, so as to distinguish the sampling artefacts from actual ecological phenomena. Hence, it is important to consider the potential biases that different sampling methods may introduce to functional trait‐based research. Foreign Language Abstract摘要: 群落組成理論 (Community assembly theory)與功能性狀方法 (Functional trait‐based approach) 促進了我們對物種分佈的理解及預測。其中, 研究員會藉評估零模型(Null model)下的多維功能性狀空間分散程度, 來衡量當地群落的主要組成機制是基於–生態位理論(Niche‐based processes) 抑或是中性理論(Neutral‐based processes)。然而, 同一群落性狀的分佈模式可能會因採樣方法的選擇而產生偏差。若這種對功能性狀的非隨機性過濾被忽略(尤其於物種豐富的節肢動物群落), 它可能會影響功能成分的呈現, 以致誤導群落組成機制的分析結果。 我們利用亞熱帶地棲螞蟻群落作例, 比較兩種常用的陸地節肢動物採樣方法– 陷阱法 (Pitfall traps) 和落葉袋採集法(Winkler extractors)。於香港的17個灌木叢和33個次生林樣地(400平方米)以零模型探討採樣過濾機制於不同的生境對功能性狀組成(六種形態特徵的群落平均值)和其多樣性(形態特徵的範圍和方差; 多維功能性狀空間的大小和填充的特性)的影響。 我們發現不同的採樣方法有著過濾螞蟻群落性狀組成和多樣性的差異。在灌木叢和森林中, 相對落葉袋採集法, 以陷阱法採得的群落特徵成分主要為體型較大﹑修長和足部較長的螞蟻。同時, 落葉袋採集法亦低估了體型的多樣性, 以及多維功能性狀空間的大小和填充的性質。 我們的結果顯示在沒有先驗知存的情況下, 住用特定的採樣方法可能會影響物種組成機制與功能性狀的剖析, 例如體型。因此, 在比較以不同採樣方法獲得的功能性狀成分時, 應進一步區分差異是來自採樣的過濾機制或實際的生態現象。研究員住用功能性狀方法時, 應當考慮及注意因選擇不同採樣方法而導致的潛在偏差。